National cultures and international competition : - Kobrak, Christopher (Cambridge University Press, 2002)
This book is first and foremost a history of Schering AG, one of Germany's best known pharmaceutical companies, from its birth as a pharmacy in the middle of the nineteenth century to the first steps of its re-birth as a multinational in 1950. It traces the various stages of Schering's development, its relationships to other chemical companies, its government, its bankers and other shareholders. As the title implies, the book also tries to put this history in the context of Schering's changing - and for the most part increasingly hostile - political, social and economic environment, which formed the context for the company's efforts to organize its personnel, develop its research and production capacity, and to internationalize its business. It argues that the evolution of Germany's system of corporate governance did not keep up with that country's ability to make technical innovations, and actually hindered Germany's ability to respond to the business challenges following World War I.